Economic impacts of bad output in agriculture: two essays for Brazilian sugarcane production - Soares, Pedro (2022)
This thesis, structured in the form of two main papers, analyzed the impacts of pollution reduction on sugarcane production in Brazil. Initially, it was investigated the contribution of technical efficiency gains to reduce the emission of greenhouse gases in sugarcane production, and also estimated the monetary compensation that producers should receive to reduce pollution. The second study analyzed, in terms of economic wellfare, the impact on markets of the sugarcane production chain the change to the mechanized harvesting system, using as an example the recent case of the state of São Paulo. The main results of the both studies indicate that efficiency gains can contribute to the greenhouse gas emissions reductions, in addition to indicating that in the transition to a mechanized harvesting scenario, the most affected sectors are the manual labor market, and the sugarcane production, indicating the need for public policies that mitigate the negative impacts of the transition, and that can contribute to efficiency gains for producers.